Teachers and Studentsâ Knowledge, Beliefs, and Observations on the Implementation of Grades 7 and 8 K-12 Mathematics Program - Cardona, Roldan S (EDUCARE, 2017)
ABSTRACT: Education at all levels is an avenue for economic, political, social, and cultural mobility. The Education for All movement, having the education for all and millennium development goals, has the ultimate aim of sustainable development. Hence, teachers and students are some of the keys to achieve the vision of K (Kindergarten) to 12 years education program from the Department of Education in the Philippines. This descriptive study sets out an initial attempt to investigate teachers and studentsâ knowledge, observations, beliefs on the benefits, and the potential threats in the implementation of grades 7 and 8 Mathematics program. From 29 selected high schools in the province of Isabela, a total of 60 Math teachers and 265 randomly selected grades 7 and 8 students participated in the study during November 2013 to May 2014. A 4-point Likert questionnaire consisting of impact statements was prepared, developed, thematically analyzed and validated. Findings revealed that Math teachers and students have equally agreed on dimensions knowledge, observations, and benefits. Teachers claimed greater potential threats of the program than students. Students and teachersâ knowledge about the program largely influences its level of implementation. The result of this study points out two relevant directions: firstly, the need for programâs regular monitoring and continuous professional training to enhance students and teachersâ understanding of the K-12 Mathematics program; and, secondly, the need to conduct related studies, explore factors of K-12 program implementation through exploratory factor analyses, and relate it to national performance through path analyses.KEY WORDS: Education for All; Knowledge, Observations, Benefits, and Potential Threats; K-12 Math Program; Level of Implementation; National Performance.===About the Author: Roldan S. Cardona is a Faculty Member at the PNU (Philippine Normal University) in North Luzon, Philippines. For academic interests, the author is able to be contacted via e-mail at: cardona.rs@pnu.edu.phSuggested Citation: Cardona, Roldan S. (2017). âTeachers and Studentsâ Knowledge, Beliefs, and Observations on the Implementation of Grades 7 and 8 K-12 Mathematics Programâ in EDUCARE: International Journal for Educational Studies, Volume 10(1), August, pp.43-52. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Article Timeline: Accepted (December 19, 2016); Revised (April 20, 2017); and Published (August 30, 2017).